Pengembangan Media Pembelajaran Puzzle Berbasis Make A Match Pada Materi Bagian-Bagian MataDan Fungsinya Pembelajaran IPAS Kelas V SDN 1 Gondang - Zanuba Aulian Nisa; Rahmad Setyo Jadmiko (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
The research was motivated by the initial findings at the time of observation even though the puzzle has been implemented, there is still a need for further development by utilizing interesting and fun media. This study aims to develop and describe the results of the validation of learning media and the application of Make A Match Based Puzzle media on the Material of Eye Parts and Their Functions of Learning Science Class V SDN 1 Gondang. This study uses a 4D development research model (Define, Design, development, Dissemination). Validity is determined by media validation, material expert validation. The validation of Puzzle media received a percentage result of 92% with the category